Expressing Alternative Modernities in a New Nation through Iban Popular Music, 1960s–1970s - Connie Lim, Keh Nie; Made Mantle, Hood (Springer, 2021)
The Iban are the largest indigenous ethnic group in Sarawak, Malaysia, constituting nearly a third of the state’s total population. They have experienced various forms of modernity since the Brooke Raj established the British colonial presence in 1841, through to its status as a British Crown colony, and then under the auspices of the Malaysian nation-state from 1963 onwards, all of which further incorporated indigenous peoples into national, regional and global relations. Under these different forms of governance—and the far-reaching social, economic, political and cultural transformations they unleashed—the Iban, as a self-defined ethnic group, have both adopted and adapted in recent decades to meet demanding challenges, most notably of nation-building and the idea of ‘independence throughMalaysia’. Drawing on a vast cultural heritage, one of the most vital means of projecting Iban responses to change has been popular music. This chapter examines a selection of Iban popular songs composed in the 1960s and 1970s which, we argue, reflected and helped shape the history of Sarawak in that era. Taking advantage of the opportunities offered by Iban-language programming on Radio Sarawak, popular music lyrics carried messages commenting on modernity: the changing relationship to ancestral lands, the impact of development, the rapid acceleration of internal migration and Sarawak’s place in the broader nation-state. In doing so, popular music lyrics offered a historical narrative of Iban people in Sarawak and what an ‘alternative modernity’ meant in a postcolonial world.